Percepção de pais de crianças surdas como agentes no desenvolvimento de linguagem de seus filhos - Pimentel, Simone Fontes de Mattos (2021)
This research aims to analyze how parents of deaf children perceive themselves as agents in their children's language development. Considering that the language development of deaf children in early childhood runs through different contexts, it is necessary to understand the determining role of the interaction between parents and children, as well as educational proposals, which benefit this process. Starting from a reflection on the education of the deaf, the listener family - deaf child relationship and interaction, based on Vygotsky's propositions, it appears that it is in social relations that the meaning of the world by the subject is possible. A qualitative study of four case studies was carried out, using the focus group strategy. The subjects were four listener families of deaf students in early childhood education at IESP-DERDIC-PUC-SP. The analysis was carried out considering three themes as axes: the family’s mode of communication, the role of the school and the way of playing. In the communication modality, there is a lack of knowledge of Libras and solutions such as simplifying or asking for support for more fluent users are evident. Communication difficulties are also interpreted as cognitive difficulties or “lack of maturity”. Regarding the role of the school, most families seem to believe that school is the place to learn new signs. In the last analyzed axis, playing, families demonstrate difficulty in identifying the relationship between understanding from a cognitive point of view, and that imposed by the language barrier, in addition to a restriction on the proposals for games, joke and storytelling. It is concluded that the families do not seem to perceive themselves as protagonists in the language development of their children, they value the bilingual school, but there is no clarity about the consequences of this choice. These findings suggest that school actions are necessary through guidance, reception, exchange and among others, contact with other families with deaf parents in order to have more contact with sign language